1984
DOI: 10.1007/bf02540816
|View full text |Cite
|
Sign up to set email alerts
|

Effect of moisture and particle size on the extractability of oils from seeds with supercritical CO2

Abstract: Moisture level and particle size of soybeans, peanuts and cottonseed were correlated with the extraction rate and yield of oil when extracted with supercritical carbon dioxide (SC‐CO2) at a constant temperature (50 C) and pressure (8000 psig). The rate of extraction and ultimate oil yields were quite low with cracked soybeans. However, good extraction rates and nearly theoretical oil yields were obtained from ground or thinly flaked (<0.010″) seeds. Moisture levels between 3% and 12% had little effect on extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
75
0
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(89 citation statements)
references
References 8 publications
11
75
0
3
Order By: Relevance
“…As reported by Fattori et al [11], both highand low-molecular-weight triacylglycerols are equally soluble in hexane and therefore no selective extractions can be performed when using organic solvents for oil extraction. Snyder et al [17] observed that the last 10-15% of soybean oil extracted by SCCO 2 had lower levels of linoleic, linolenic and palmitic acids and higher levels of oleic and stearic acids compared to the rest of the fractions. Similarly, Fattori et al [11] reported that the last 20% of canola oil obtained during SCCO 2 extraction showed higher concentrations of behenic and lignoceric acids.…”
Section: Chemical Characterization Of Extracted Oilsmentioning
confidence: 98%
“…As reported by Fattori et al [11], both highand low-molecular-weight triacylglycerols are equally soluble in hexane and therefore no selective extractions can be performed when using organic solvents for oil extraction. Snyder et al [17] observed that the last 10-15% of soybean oil extracted by SCCO 2 had lower levels of linoleic, linolenic and palmitic acids and higher levels of oleic and stearic acids compared to the rest of the fractions. Similarly, Fattori et al [11] reported that the last 20% of canola oil obtained during SCCO 2 extraction showed higher concentrations of behenic and lignoceric acids.…”
Section: Chemical Characterization Of Extracted Oilsmentioning
confidence: 98%
“…Generally, the solubility of triglycerides depends upon the density of carbon dioxide, which can be manipulated through the pressure variation. Snyder et al (1984) found that the fractionation of soybean oil in supercritical carbon dioxide extraction at 550 bar and 50°C only occurred in the last 10-15% of the oil extracted in which the composition of fatty acid in triglycerides varied.…”
mentioning
confidence: 99%
“…Shen et al (27) observed similar behavior in the case of application to rice bran oil extraction. Gómez et al (28) proposed that the change was due to variations in the physical properties of CO 2 , particularly the density which is closely related to the solvent capacity.…”
Section: Extraction Of Salmon Roe Lipids With Scf-comentioning
confidence: 99%